2020
DOI: 10.1016/s1473-3099(20)30310-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphadenopathy in patients with severe COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 5 publications
3
37
2
1
Order By: Relevance
“…This may suggest that lymphadenopathy could be an independent imaging biomarker of the disease, similar to what demonstrated for other infections (Chadburn et al 1989). Indeed, based on limited data, lymphadenopathy has been suggested as a prognostic marker of COVID-19 infection severity (Valette et al 2020) and a predictor of a worse outcome (Sardanelli et al 2020). In view of the grave clinical outcome of our patient, there may be an argument in support of a further prognostic role of higher SUVmax values of FDG positive nodal disease, as a biomarker which could herald a more severe case of the infection with the virus.…”
Section: Discussionsupporting
confidence: 52%
“…This may suggest that lymphadenopathy could be an independent imaging biomarker of the disease, similar to what demonstrated for other infections (Chadburn et al 1989). Indeed, based on limited data, lymphadenopathy has been suggested as a prognostic marker of COVID-19 infection severity (Valette et al 2020) and a predictor of a worse outcome (Sardanelli et al 2020). In view of the grave clinical outcome of our patient, there may be an argument in support of a further prognostic role of higher SUVmax values of FDG positive nodal disease, as a biomarker which could herald a more severe case of the infection with the virus.…”
Section: Discussionsupporting
confidence: 52%
“…A large proportion of patients with COVID-19 were found to have enlarged intrathoracic lymph nodes, which is in distinction to the initial report from China suggesting only 6% incidence of lymph node enlargement in hospitalised patients. 41 Recent correspondence by French investigators 42 showed up to 66% incidence of lymph node enlargement in COVID-19 patients admitted to intensive care unit. This indicates controversy surrounding the issue of lymph node enlargement, which could be partly due to differences in study cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The thorax where the mediastinal lymphadenopathy if found with lymph node enlargement that can be potentially detected by CT imaging suggesting expression of the inflammatory response to the infection [46][47][48]. (2) In the gastrointestinal tract where distended fluidfilled small and large bowel loops and surrounding stranding are demonstrated on enhanced CT [30].…”
Section: Potentials Of Virtual Autopsy Findings In Extrapulmonary Manmentioning
confidence: 99%